2018
DOI: 10.3390/en11081944
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mud Pressures for the Stability of Wellbores Drilled in Transversely Isotropic Rocks

Abstract: Serious borehole instability problems are often related to the presence of weakness planes in rock formations. In this study, we investigated the stability of wellbores drilled along a principal direction and parallel to the weakness planes. We used three different strength criteria (weakness plane model, Hoek and Brown and Nova and Zaninetti) to calculate the mud pressures to avoid slip and tensile failure along the weakness planes. We identified the orientation of the weakness planes that generate the most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 49 publications
6
21
0
Order By: Relevance
“…Insitu stress and bedding plane orientations should therefore be correctly accounted for to assess the wellbore stability. Note that wellbore orientation c is similar to one of cases considered in Deangeli and Omwanghe (2018). Although the elastic anisotropy and initial undrained pore pressure response are not considered by them, the failure regions predicted for the wellbore orientation are consistent with their results.…”
Section: )supporting
confidence: 70%
See 1 more Smart Citation
“…Insitu stress and bedding plane orientations should therefore be correctly accounted for to assess the wellbore stability. Note that wellbore orientation c is similar to one of cases considered in Deangeli and Omwanghe (2018). Although the elastic anisotropy and initial undrained pore pressure response are not considered by them, the failure regions predicted for the wellbore orientation are consistent with their results.…”
Section: )supporting
confidence: 70%
“…For example, a horizontal well drilled in the maximum horizontal stress direction (orientation g) does not show bedding plane failures, while other two horizontal wells (orientations c and e) show noticeable failures. Inclination of the bedding planes also affects the failure region (e.g., Deangeli and Omwanghe 2018). Insitu stress and bedding plane orientations should therefore be correctly accounted for to assess the wellbore stability.…”
Section: )mentioning
confidence: 99%
“…Based on the process of offshore gas reservoir production, the wellbore pressure distribution model in the process of producing water-bearing natural gas is established [43][44][45]:…”
Section: Wellbore Pressure Modelmentioning
confidence: 99%
“…Another researcher established a weak plane model and discovered that it is effective in predicting stratigraphic wellbore failure, except for obvious loose or plastic formations [21]. Therefore, it is determined that the direction of the weak plane is closely related to wellbore failure [22]. As a result, the isotropic wellbore stress distribution model is established [23,24], and it is found that Poisson's ratio has little influence on borehole stability in shale formation [25,26].…”
Section: Introductionmentioning
confidence: 99%